2019
DOI: 10.1111/jnc.14917
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1‐phosphate but not Fingolimod protects neurons against excitotoxic cell death by inducing neurotrophic gene expression in astrocytes

Abstract: Abbreviations used: AD, Alzheimer's disease; BBB, blood-brain barrier; BDNF, brain-derived neurotrophic factor; DMEM, Dulbecco's modified Eagle's medium; DMSO, dimethyl sulfoxide; ERK, extracellular signal regulated kinase; FBS, fetal bovine serum; FTY720-P, FTY720-phosphate; HBEGF, heparin-binding epidermal growth factor-like growth factor; LIF, leukemia inhibitory factor; NMDA, N-methyl-d-aspartate; PDGFB, platelet-derived growth factor; PI, propidium iodide; RRID, research resource identifier; S1P, sphingos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Mature HB-EGF signals through EGFR, ErbB4 and a newly defined N-arginine dibasic convertase, but may also be able to induce ErbB2 through heterodimerization ( 214 , 225 227 ). In astrocytes, upregulation of HBEGF mRNA has been observed in response to sphingosine-1-phosphat (S1P)-receptor activation by S1P or S1P receptor modulator fingolimod ( 92 , 93 ). This may be dependent on combined S1P1R and S1P2R signaling and the activation of the immediate early transcription factors ERG1 and AP1, indicating that astrocyte-derived HB-EGF is part of a rapid response mechanism that counteracts pro-inflammatory astrocyte functions ( 93 ).…”
Section: Protective Effects Of Reactive Astrocytes Following Cns Insumentioning
confidence: 99%
See 2 more Smart Citations
“…Mature HB-EGF signals through EGFR, ErbB4 and a newly defined N-arginine dibasic convertase, but may also be able to induce ErbB2 through heterodimerization ( 214 , 225 227 ). In astrocytes, upregulation of HBEGF mRNA has been observed in response to sphingosine-1-phosphat (S1P)-receptor activation by S1P or S1P receptor modulator fingolimod ( 92 , 93 ). This may be dependent on combined S1P1R and S1P2R signaling and the activation of the immediate early transcription factors ERG1 and AP1, indicating that astrocyte-derived HB-EGF is part of a rapid response mechanism that counteracts pro-inflammatory astrocyte functions ( 93 ).…”
Section: Protective Effects Of Reactive Astrocytes Following Cns Insumentioning
confidence: 99%
“…In astrocytes, upregulation of HBEGF mRNA has been observed in response to sphingosine-1-phosphat (S1P)-receptor activation by S1P or S1P receptor modulator fingolimod ( 92 , 93 ). This may be dependent on combined S1P1R and S1P2R signaling and the activation of the immediate early transcription factors ERG1 and AP1, indicating that astrocyte-derived HB-EGF is part of a rapid response mechanism that counteracts pro-inflammatory astrocyte functions ( 93 ). Indeed, it has been suggested that HB-EGF suppresses the nuclear translocation of NF-κB by inhibition of IκB kinase (IKK) mediated inhibitor of κB (IκB) degradation ( 222 ).…”
Section: Protective Effects Of Reactive Astrocytes Following Cns Insumentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingosine-1-P, by stimulating both S1PR-1 and S1PR-2, may induce gene expression encoding for the production of protective astrocyte neurotrophic factors, not achieved by S1PR-1 modulation alone [ 58 ]. Bi-receptor S1PR-1 and S1PR-2 stimulation [ 59 ] appears to be necessary to up-regulate neurotrophic mRNA expression, which only takes place in astrocytes [ 60 , 61 ]. To date there are no pharmacological agents of which we are aware that operate jointly or exclusively at both S1PR-1 and S1PR-2 under investigation as potential medications for MS, yet the importance of regulating astrocyte proliferation and astrogliosis would be reasons enough to examine agents that can synergistically modulate both receptor subsets.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…signaling via G 13 and the small G-protein RhoA that upregulates and activates the transcription factors Fos and Jun, which regulate the transcription of LIF [122].…”
Section: Astrocytesmentioning
confidence: 99%